2001
DOI: 10.1002/1097-4652(200002)186:2<153::aid-jcp1016>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Role of transforming growth factor beta in cancer

Abstract: Transforming growth factor beta (TGF-beta) is an effective and ubiquitous mediator of cell growth. The significance of this cytokine in cancer susceptibility, cancer development and progression has become apparent over the past few years. TGF-beta plays various roles in the process of malignant progression. It is a potent inhibitor of normal stromal, hematopoietic, and epithelial cell growth. However, at some point during cancer development the majority of transformed cells become either partly or completely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(123 citation statements)
references
References 177 publications
(105 reference statements)
1
119
0
3
Order By: Relevance
“…However, it is generally accepted that TGF-b1 has a key role in inducing myofibroblast differentiation, and high levels of the cytokine are usually associated with MF-containing lesions (Tuan and Nichter, 1998). TGF-b1 is frequently detectable in SCC, particularly in the more advanced stages of tumour progression, and relatively high concentrations of TGF-b1 are usually found in tumour stroma (Pasche, 2001). Recently, Bauer et al (2002) showed that keratinocytes genetically modified to produce activated TGF-b1 induced collagen type I gene expression in dermal fibroblasts in a coculture system.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is generally accepted that TGF-b1 has a key role in inducing myofibroblast differentiation, and high levels of the cytokine are usually associated with MF-containing lesions (Tuan and Nichter, 1998). TGF-b1 is frequently detectable in SCC, particularly in the more advanced stages of tumour progression, and relatively high concentrations of TGF-b1 are usually found in tumour stroma (Pasche, 2001). Recently, Bauer et al (2002) showed that keratinocytes genetically modified to produce activated TGF-b1 induced collagen type I gene expression in dermal fibroblasts in a coculture system.…”
Section: Discussionmentioning
confidence: 99%
“…1). Loss of growth responsiveness to TGF-␤ is extremely common in tumor cells (49). Interestingly, this failure of TGF-␤ to inhibit cell growth was not due to a loss of TGF-␤ receptors or defects in the early portions of TGF-␤ signaling.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition was noted because of an accumulation of the pro form of TGF-␤1 in PDX-transfected cells, a fact that could not be observed in the vector alone-transfected cells. TGF-␤1 is known for its role in activating MMP-2 in normal and cancer cells (29,30) and for enhancing invasion and metastasis in several human and experimental cancer models (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%